STEM-05. NEURAL G0: A NOVEL QUIESCENT-LIKE STATE IN PROLIFERATING HUMAN NEURAL STEM AND GLIOBLASTOMA TUMOR CELLS. (11th November 2019) - Feldman, Heather; Arora, Sonali; Hoellerbauer, Pia; Pollard, Steven; Patel, Anoop; Plaisier, Christopher; Paddison, Patrick
Abstract: Single cell (sc) genomic technologies are rapidly transforming our understanding of cellular states in normal and diseased tissues. Here, we applied scRNA-seq to cultures of proliferating human neural stem cells (NSCs) to better understand the relationship between cell cycle dynamics and developmental gene expression. This analysis revealed both conventional cell cycle states (S, G2, M) and novel G1 and G0-like states. Of note, we identified a Neural G0 phase representing a subpopulation enriched for expression of genes associated with adult quiescent NSCs, including CLU, HOPX, ID3, OLIG2, PTN, SYT11, S100B, SOX9, PTPRZ1, and TTYH1 . Remarkably, by applying our hNSC cell cycle phase classifier to human glioblastoma (GBM) tumors, we found that Neural G0 subpopulations as a prominent tumor-specific cellular subclass of GBM tumors, which, similar to NSCs, does not overlap with proliferative cell cycle phases. We further identified modulators of Neural G0 via CRISPR-Cas9 screens, revealing highly significant enrichment for tumor suppressor genes associated with brain tumors. In depth analysis of five of these Neural G0 modulatory genes, including CREBBP, NF2, PTPN14, TAOK1, or TP53, revealed that they promote compartmentalization of G0/G1 phase and expression of genes associated with Neural G0. Our results suggest that Neural G0 is a dynamic cell state in mammalian NSCs, that a subset of GBM cells maintain and is modulated by genes commonly found altered in GBM.